1997
DOI: 10.1007/s003300050106
|View full text |Cite
|
Sign up to set email alerts
|

Radiologists and visual acuity

Abstract: Visual acuity (VA) and potential risks to the radiologist's eyesight have been relatively neglected subjects in the radiological literature. This study comprises two parts, the first consisting of a questionnaire on this subject sent to a random sample of 480 practising radiologists in the United Kingdom, and the second, a spot check of the VA of radiologists in our department. Of questionnaires, 73 %were returned. Of respondents, 76 % felt that ionising radiation could affect their vision, but only 13 % used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Safdar et al [8] determined that 16.7% of American and Pakistani radiologists could not remember ever having had VA testing. Among British radiologists, Quaghebeur et al [9] found that 13.4% had had VA testing as a result of ''headaches and problems related to work'', but that among the 41% of people to have had an occupational health assessment, only 4% had undergone eye testing as part of this. In the same study it was determined that 20% of practising radiologists may benefit from either the use of corrective lenses or the updating of a current corrective lens prescription, given that they had a VA of ,6/6 [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Safdar et al [8] determined that 16.7% of American and Pakistani radiologists could not remember ever having had VA testing. Among British radiologists, Quaghebeur et al [9] found that 13.4% had had VA testing as a result of ''headaches and problems related to work'', but that among the 41% of people to have had an occupational health assessment, only 4% had undergone eye testing as part of this. In the same study it was determined that 20% of practising radiologists may benefit from either the use of corrective lenses or the updating of a current corrective lens prescription, given that they had a VA of ,6/6 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Of those who were aware of it, 98% felt it was relevant to radiologists for ''personal or safety reasons and for potential effects on work efficiency'' [9]. A large majority (82%) of UK radiologists would be amenable to undergoing regular eye testing, while a slightly smaller number (71%) felt that such testing should be mandatory for a radiologist during their career [9]. There are precedents to establish mandatory eye testing for professionals in whom good VA is felt to be important to their job.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of 480 UK consultant radiologists revealed that 71% of respondents supported regular vision testing for radiologists 18. These surveys demonstrate that those working in the field of radiology identify good visual function as critical to radiological practice.…”
Section: What Is Known About Vision and Visual Acuity In Other Medicamentioning
confidence: 97%